Mercury level determination of oysters from Cavite - Pengson, Erinn Ann S.
The level of mercury in oyster collected from different culture sites were determined in the study. Validation test was done to assess the efficiency of the instruments for the chosen technique. Fresh samples coming from the culture sites were spiked with 0.01 µg Hg and subjected to analysis. Percent recovery was found to be 97% and 62%, respectively, for two runs.Using Flameless Atomic Absorption Spectrophotometric Method, the level of mercury in fresh samples were found to be approximately <0.0500 ppm mercury in Naic, Cavite and 0.0207 ppm, 0.134 ppm and 0.073 ppm mercury for Site A, B, C, respectively in Bacoor, Cavite. Effect of heat treatment (i.e. boiling and steaming) on the level of Hg in oyster were likewise determined. It was observed that Hg levels was reduced from 0.207 ppm to 0.116 and 0.141 for boiling and steaming, respectively.